PENGARUH GERAKAN SABUK HIJAU (THE GREEN BELT MOVEMENT) TERHADAP KEBIJAKAN PEMERINTAH KENYA DALAM MENJAGA KEASRIAN LINGKUNGAN HIDUP DI KENYA - Desi Efrika Devita; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research discusses an environmentalist organization in one of the countries in Africa that called The Green Belt Movement organization that based in Nairobi, Kenya. The Green Belt Movement is one of non-governmental organization which attempt to make a change and protection to the environment maintenance and raise an awareness of the public to also preserve and maintain the environment.The research applies qualitative methods, and case study in this research the data collected through library research, literature studies, official documents, academic journal, mass media.The unfavorable environmental phenomena, such as frequent illegal logging, the forest erosion, and the lack of public awareness in maintaining and preserving the environment makes the Green Belt Movement organization strove to contend and solve the environment problems. The integration of environmental issues into international relations is like the introductory texts that tend to simplify into some possibilities. In this case, The Green Belt Movement is an organization formed to handle many environmental problems that need an attention. Keywords: The Green Belt Movement, Organization, Forest destruction, Environment.